Occurrence of Talaromyces marneffei in wild mammals in Portugal - Matos, Ana Cristina (2020)
Talaromyces marneffei is a thermally dimorphic fungus that is endemic in some parts of Asia causing a fatal systemic mycosis in immunocompromised patients. The aim of this study was to evaluate the occurrence of T. marneffei in the fur of wild mammals in Portugal.